Sucker-like structures on the pathogenic amoeba Naegleria fowleri. - John, D T (1984)
Using scanning electron microscopy, we observed sucker-like structures on amoebae of 13 human isolates of Naegleria fowleri. The number of suckers per amoeba seemed to vary according to the virulence of the strain. We propose the term amoebastome to describe this unique sucker-like structure of N. fowleri.